Evaluating the Effectiveness of Japan’s Climate Change Mitigation and Clean Technology Development Policies - I Ihara; R Zhao; A H Pandyaswargo; H Onoda (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
The energy sector has been the highest contributor of green-house gases (GHG) emission in Japan. To reduce GHG emissions, the development and applications of cleaner technologies supported by effective policies are required. In this study, the effectiveness of Japanese government policies related to climate change mitigation especially in the technology development sector was analyzed. To do so, two methodologies; 1) results-based approach (RBA) and 2) case-based approach (CBA) will be combined to test the effectiveness of government policies. This combination was conducted to fill the missing data required to conduct the two methodologies. The merging of the two methodologies produced indexes where the proximity of the performance of each policy measured to it would determine its effectiveness. In order to verify the results, the number of projects related to the policy took place over the years was also observed. The results show that the most effective policies were related to the following technologies: 1) Energy management, 2) Biomass energy production, and 3) Electric power storage.